Analysis of DNA Polymorphism in SRY Gene of Madura Cattle Populations - Tety, Hartatik; T.S.M, Widi; S.D, Volkandari; D, Maharani; Sumadi, Sumadi (Scien cedirect, 2013)
The aim of this research was to assess the SRY-gene polymorphism in Madura cattle populations and the hybrids of Madura cow with Limousin bull. We investigated the specific markers of the paternally transmitted Y- chromosome for the direct detection of male-mediated introgression. We performed PCR–RFLP to identify the polymorphism of Y-chromosomes in 17 Madura cattle from Pamekasan district, 4 conserved Madura cattle from Sapudi Island and 22 Limousin x Madura crossbred cattle from Pamekasan. The result showed the polymorphisme of Y-chromosome at the locus was recognized by BfaI restriction enzymes at the position 432 bp and 544 bp. Using the same restriction enzyme, this study identified 68.18% of Limousin x Madura crossbred cattle was in the sequence of Y-chromosome. The high numbers of BfaI site restriction in the sequence of Y-chromosome due to the introduction Limousin bull by artificial insemination. For those, the preservation of pure Madura cattle as one of animal genetics resources in Indonesia should be a concern.